Agricultural innovation platform as a tool for development oriented research: Lessons and challenges in the formation and operationalization - Tenywa, M.M.; Rao, K.P.C.; Tukahirwa, J.M.B.; Buruchara, Robin Arani; Adekunle, A.A.; Mugabe, J.; Wanjiku, C.; Mutabazi, S.; Fungo, B.; Kashaija, N.I.M.; Pali, Pamela N.; Mapatano, S.; et al. (2011)
The emergence of Integrated Agricultural Research for Development (IAR4D) presents an opportunity to address any development problem. It involves innovative principles and an integrated research agenda while recognizing the need for greater organizational capacities among stakeholders in agriculture. Operationalization of IAR4D revolves around successful establishment and operation of an Agricultural Innovation Platform (AIP). Agricultural Innovation Platforms are being implemented in Lake Kivu Pilot Learning Site (LKPLS) of the Sub-Saharan Africa Challenge Programme, covering three countries (Uganda, Rwanda and Democratic Republic of Congo) with widely differing social political environments to address agricultural development challenges. This paper presents the processes, general guidelines lessons and experiences pertaining to “good practices” for organising and forming AIPs in the LKPLS. The life of AIPs covers three phases, namely; pre-formation, formation and post formation. The lessons and experiences are shared across 6 stages of AIP formation, namely; Identification of a research and developmental challenge(s), Site selection, Consultative and scoping study, Visioning and Stakeholder analysis, Development of action plans and Implementation of the action plans. Emerging lessons highlight AIPs as grounds and pillars for multi-level, multi-stakeholder interactions to identify, understand and address a complex challenge, concomitant emerging issues and learning towards achieving the agreed vision. Agricultural Innovation Platform formation is a dynamic, highly context specific process that incorporates all essential ingredients for successful innovation at once and provides an opportunity for local innovations to bear while at the same time nourishing on introduced innovations. In AIP formation, the recognition and value of indigenous knowledge and capitalization on prevailing policy, institutional setting and involvement of local leadership is vital. The form, nature and time taken by AIP formation process depends on both the conceptual and local context, quality of facilitation, socio-economic, culture, biophysical, political environment in which a common challenge and/or opportunity is identified and on the capacity of stakeholders to comprehend the Innovation Systems Approach (ISA). The process of AIP formation was faster in creating win-wins when market led. Strong leadership, strategic partnership, information flow, interactions and dealing with recurrent challenges during the AIP formation process are critical in fostering innovations. The major challenges included capacitating the stakeholders in requisite skills and dealing with persistent “handout-syndrome”.